La construcción de instrumentos musicales en miniatura como recurso didáctico para facilitar los procesos pedagógicos – musicales en el grado 4° de básica primaria en el colegio George's Noble School en la ciudad de Montería - Córdoba (2020)
This monograph is important because it intertwines ways of knowing a musical instrument, not only focusing on its performance or the student's musical abilities. In today's schools, in the area of music, pedagogy focuses on teaching the technique very briefly and making an assembly with the rest of the room. The importance of the music teacher is that you listen well and that the children like it, even they want to learn quickly and easily, that requires less time spent having a "good" result. This project goes beyond that, it seeks that the child knows his instrument in all the forms, the parts, the material with which it was made, the teacher teaches the work of the luthier, understands the reason for the technique, since he understands the Its organology has a more open perception of the instrument.